IMPLEMENTASI PROGRAM BTQ PADA MAHASISWA JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Tahir, Andi (Jurnal Pendidikan Kreatif, 2021)
The main problem of this research is how to implement the implementation of the BTQ Program in improving the ability to read and write the Qur'an in students majoring in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. The main problem is divided into three sub-problems or research questions, namely: BTQ in improving the ability to read and write the Qur'an in students majoring in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar and how is the ability to read and write the Koran in the Department of Islamic Education, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar and how are the supporting factors and obstacles to the BTQ program in the Department of Islamic Education, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. This type of research is a qualitative research / field research with the research approach used is a sociological, theological, pedagogical and psychological approach. The sources of research data obtained directly from the director of BTQ, lecturers and students as well as administrative staff. Furthermore, the data collection methods used were observation, interviews, and documentation as well as searching various literatures or references. Then the data processing and analysis techniques were carried out through three stages, namely data reduction, presentation, and conclusion drawing. The results of this study show that: An overview of the BTQ program in the Department of Islamic Religious Education, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar consists of 3 stages including, 1) Introduction which includes preparing students psychologically and physically, praying, doing attendance, apperception, 2) Activities The core includes providing a simulation of how to write the Koran, giving examples of how to read the Koran, listening to student readings and classifying students' abilities to apply peer tutoring methods, 3) closing, including concluding learning outcomes from beginning to end, follow-up , giving students the opportunity to ask questions, then closed with a prayer. The form of the assessment of reading and writing the Qur'an at the Department of Islamic Religious Education, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar was analyzed through 3 stages including assessment of how to read, get used to writing and when you are proficient in reading and writing which are in accordance with the rules of tajwid then in invite or be given permission to add to the memorization of the Qur'an. The supporting and inhibiting factors, the supporting factors include,, the existence of guidebooks and motivation and the program becomes a mandatory activity for students, the inhibiting factors include, lack of motivation and a lot of activity, talent and interest problems, fales voice problems, time management, methods and the environment .